MEOX2 homeobox gene promotes growth of malignant gliomas - Schönrock, Anna; Heinzelmann, Elisa; Steffl, Bianca; Demirdizen, Engin; Narayanan, Ashwin; Krunic, Damir; Bähr, Marion; Park, Jongwhi; Schmidt, Claudia; Özduman, Koray; Pamir, M Necmettin; Wick, Wolfgang; et al. (Neuro-Oncology, 2022)
Glioblastoma (GBM) is an aggressive tumor that frequently exhibits gain of chromosome 7, loss of chromosome 10, and aberrantly activated receptor tyrosine kinase signaling pathways. Previously, we identified Mesenchyme Homeobox 2 (MEOX2), a gene located on chromosome 7, as an upregulated transcription factor in GBM. Overexpressed transcription factors can be involved in driving GBM. Here, we aimed to address the role of MEOX2 in GBM.Patient-derived GBM tumorspheres were used to constitutively knockdown or overexpress MEOX2 and subjected to in vitro assays including western blot to assess ERK phosphorylation. Cerebral organoid models were used to investigate the role of MEOX2 in growth initiation. Intracranial mouse implantation models were used to assess the tumorigenic potential of MEOX2. RNA-sequencing, ACT-seq, and CUT&Tag were used to identify MEOX2 target genes.MEOX2 enhanced ERK signaling through a feed-forward mechanism. We identified Ser155 as a putative ERK-dependent phosphorylation site upstream of the homeobox-domain of MEOX2. S155A substitution had a major effect on MEOX2 protein levels and altered its subnuclear localization. MEOX2 overexpression cooperated with p53 and PTEN loss in cerebral organoid models of human malignant gliomas to induce cell proliferation. Using high-throughput genomics, we identified putative transcriptional target genes of MEOX2 in patient-derived GBM tumorsphere models and a fresh frozen GBM tumor.We identified MEOX2 as an oncogenic transcription regulator in GBM. MEOX2 increases proliferation in cerebral organoid models of GBM and feeds into ERK signaling that represents a core signaling pathway in GBM.
Online veröffentlicht: 25. April 2022
Gesehen am 07.08.2025